Impact of sodium ingestion during exercise on endurance performance: a systematic review - McCubbin, A. J.; Costa, R. J. S. (International Journal of Sports Science, 2018)
Sports nutrition guidelines frequently encourage sodium ingestion during endurance exercise, and much work has been undertaken to quantify sweat sodium losses during exercise. However, current guidelines for sodium do not recommend specific quantities, nor provide justification for the effectiveness of sodium to improve endurance performance. A systematic review was undertaken using six databases (CINAHL, Embase, Medline Ovid, Scopus, SPORTDiscus, and Web of Science) to determine the effect of sodium ingestion during exercise on endurance performance. Five studies met the inclusion criteria. They varied in quantity of sodium consumed (280 to 900mg/h), ingestion method (capsules or solutions), fluid intake (programmed or ad libitum) and performance outcomes (time trial, distance-test, time to exhaustion following steady state exercise, and finish time in an organized competition). Only one study reported a significant benefit from sodium ingestion (504mg/h) of 7.8%. All other studies found no significant effect of sodium on performance. Several limitations were found, including different ambient conditions across study days, ad libitum carbohydrate intake that was not reported, and performance measured during an organized competition where other factors may have influenced finish time. No study measured performance in hot ambient conditions (e.g., =30°C), and no study quantified each participant`s sweat sodium losses beforehand, thus providing sodium intake as a proportion of expected losses. It is concluded that there is currently minimal evidence that sodium ingestion during exercise improves endurance performance. The limited number and quality of existing studies indicates a need for future work in this area.